Familiares cuidadores na condição crônica estomia - Cerencovich, Elisangela (2014)
The family caregiver is the primary care provider, mobilizing action and mediator of interpersonal relationships of people with ostomy, whether in your own family or in the agencies and services. This study aimed to understand the context of family caregivers in chronic condition ostomy. The theoretical framework adopted was sociocultural. The context of the study was a clinic nurse who takes care of a people with stomas located in Cuiaba , Mato Grosso. Data collection was conducted from April 2012 to May 2013 and has occurred in two distinct steps with different strategies. The first occurred with circle community therapy, attended by eight families, and the second consisted of six semi-structured interviews. The data were subjected to thematic analysis. Each step allowed to identify a theme, the first titled The family caregiver in the context of the person being stoma. In this step, the family takes care in home context,, which is related to the domestic environment, family relations and the demands of feeding, hygiene and comfort, and in public context which refers to relations seeking professional attention, governmental social support needed to continuity of care. As they told overloads require care institutions. The CIT ( Community Integrative Therapy) as a data collection strategy proved powerful in highlighting the sociocultural context of family caregivers. The second, Meanings of experience in being a family caregiver in chronic condition stoma showed that the meanings of the experience of the family relate to the illness marked by initial path in health institutions through admissions, ownership of medical terms, physical manifestations process, risk death impact the completion of the stoma, the implications are significant for the perception requiring care. Biological, social and cultural repercussions describe how remarkable prejudice, misinformation, common spaces, especially public toilet and offsets in search of devices. While expressing grief give positive meaning to the experience. Therefore, the subjects showed that the family caregiver provides care mobilizing actions mediated movements, identity and otherness, responsibility, plasticity, projects and concern for each other.